[Transition of myocardial ischemia to heart failure] - Ertl, G; Fraccarollo, D; Gaudron, P; Hu, K; Laser, A; Neubauer, S; Schorb, W (1998)
Myocardial ischemia results in myocardial dysfunction. Recovery may be delayed ("stunning"), or persistent if perfusion remains reduced ("hibernation") and ischemia may go on to necrosis, thus, contributing to chronic heart failure. In addition, myocardium not directly affected by ischemia may undergo adaptive processes like hypertrophy and dilatation, which may result in chronic left heart failure. This process is characterized by hemodynamic, neurohumoral, and progressive morphologic changes of the heart which are closely interrelated. Hemodynamic changes basically consist of an increase in left ventricular filling pressure and a decrease in global ejection fraction, and, in most cases years after myocardial infarction, in an increase in systemic vascular resistance and right atrial pressure. Neurohumoral changes consist of an increase in plasma catecholamines, atrial natriuretic factor and vasopressin, and in an activation of the renin-angiotensin-system. Plasma endothelin-1 was recently reported to be increased in patients with heart failure, and prognosis was related to endothelin levels. Diminished response of vessels to endothelium (EDRF/NO) dependent vasodilatation suggests impairment of vascular endothelium in heart failure. Local changes of cardiac neurohumoral systems could contribute to structural changes of the heart, e.g., systemic activation to hemodynamic changes. Structural changes of the heart are characterized by an increase in volume and thickness of surviving myocardium and an expansion of ischemic and necrotic myocardium. Molecular control of these processes which include various cell types, such as cardiomyocytes and cardiofibroblasts, are currently an issue of intense research and could result in specific therapeutic importance.